New organisations and new workplaces: Implications for workplace design and management. Issue 1 (4th April 2016) - Harris, Rob
Abstract : Purpose: The purpose of this paper is to outline key changes occurring within office occupier businesses that will have a medium- to long-term impact upon the nature and design of the office workplace, and the implications for the corporate real estate manager. Design/methodology/approach: The paper is based upon research involving detailed consultations with corporate occupiers in the City of London, as well as representatives of the property supply chain. This has been developed here to include practical experience and to relate the lessons of the work directly to corporate real estate management. Findings: The findings suggest major changes are taking place in the demand profile of office occupiers, in terms of both quantitative and qualitative demand for space. There are a number of practical implications arising from the findings, not least the need for investors to consider the appropriateness of current standards for base building design and fit-out in contemporary offices, and the need for corporate real estate management to adapt. Practical implications: The paper contains a number of implications arising from the changing workplace for the corporate real estate management profession. Originality/value: The paper reflects direct practical experience and the output of primary research and consulting. It is also highly relevant: while much has been written about agile working, much less has covered the practical implications for building design and corporate real estate management.